Industrial wastewater treatment using venture injector type Micro-bubble aeration as a reduction of dissolved Iron (Fe2+) levels - Efendi, Dimas Amirul Mukminin Nur; Ramandani, Adityas Agung; Cendekia, Devy; Hanifah, Windia (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Water quality problems that are often encountered, especially by-product wastewater resulting from industrial processes that do not meet the requirements for wastewater quality standards. Iron levels in wastewater can cause the water to turn brownish yellow and produce an unpleasant odor, which of course has a big impact on the environment. Therefore, it is necessary to implement a treatment process to reduce the iron level in the water, ensuring that the water is safe when discharged into the environment. The purpose of this research is to analyze the initial parameters of temperature, pH, TDS, TSS, dissolved oxygen (DO) and dissolved iron (Fe2+) in industrial waste water and then wanted to know whether the venture injector type micro bubble aeration process was able to increase the value of dissolved oxygen (DO) and decrease the dissolved iron content (Fe2+) in wastewater and to know the micro bubble type aeration process Venture injectors are the best to use. The research was conducted with an experimental design using a completely randomized design (RAL) with two factors: air flow (2 LPM, 4 LPM, and 6 LPM) and aeration time (0 minutes, 15 minutes, 30 minutes, 45 minutes, and 60 minutes), each with two repetitions. In the results of the initial parameter analysis, the pH value was 8.02 (alkaline), the temperature value was 28°C, the TDS value was 1548.3 mg/L, the TSS value was 291 mg/L, the DO value was 0.1 mg/L and dissolved iron (Fe2+) of 7.453 mg/L. After conducting research, it was found that the venture injector type micro bubble aeration process was able to increase the value of dissolved oxygen (DO) and reduce dissolved iron (Fe2+) in industrial waste water, the best increase in dissolved oxygen (DO) at 6 LPM air flow for 60 minutes was able to increase oxygen dissolved (DO) to 2.40 mg/L. The most efficient and effective reduction in the value of dissolved iron (Fe2+) at 6 LPM air flow with a time of 15 minutes was able to reduce the value of dissolved iron by 84.42%.